A kinetic enhanced tuck jump assessment exposes residual biomechanical deficits in female athletes 9 months post anterior cruciate ligament reconstruction - Kember, L. S.; Riehm, C. D.; Schille, A.; Slaton, J. A.; Myer, G. D.; Lloyd, R. S. (The Journal of Strength and Conditioning Research, 2024)
Addressing biomechanical deficits in female athletes after anterior cruciate ligament reconstruction (ACLR) is crucial for safe return-to-play. The tuck jump assessment (TJA) is used to identify risks associated with ACL injury, yet its fundamental analyses lack the ability to explore landing forces. Kinetic asymmetries during the TJA were assessed in athletes with ACLR (n = 38) and matched healthy controls (n = 21) using discrete time-point analysis and statistical parametric mapping (p < 0.05). The ACLR group performed fewer jumping cycles with distinct kinetic differences, including longer ground contact time (g = 1.45), larger peak center of mass displacement (g = 1.29), and lower peak vertical ground reaction force (VGRF) (g = -2.05) and relative leg stiffness (g = -1.51). Greater interlimb kinetic asymmetries were evident in the ACLR group for VGRF (g = 0.84), relative leg stiffness (g = 0.85), average loading rate (g = 0.84), peak braking force (g = 0.85), and time of braking (g = 0.80) and propulsive peaks (g = 1.04). Moderate differences in VGRF favored the uninvolved limb of the ACLR group for the majority (2-100%) of the stance phase of TJA (d = -0.52). Distinct jump-landing strategies between ACLR athletes and healthy controls were revealed during the TJA, which may indicate compromised stretch-shortening cycle function. Findings highlight the need for targeted rehabilitation to foster greater kinetic symmetry in jump-landing performance and underscore the importance of longitudinal and progressive monitoring for optimized return-to-play outcomes in athletes after ACLR.